Emotions against anatomical dissection in the Degree of Speech and Language Therapy - Criado-Álvarez, Juan José; Mohedano, Alicia; González, Jaime; Romo-Barrientos, Carmen (Revista de Investigación en Logopedia, 2016)
Practices with human cadaver dissection have a long tradition and are a basic part of the teaching of human anatomy. However they can be a stressful experience for the student, which may pose a high level of anxiety. The aim of this study was to determine the attitudes, reactions and fears of students in first degree course of Speech and Language against the dissecting room. This is a cross-sectional study conducted before-and-after the first students from year Logopedia of Castilla-La Mancha University (Spain) who had never participated in a practice of dissection. Prior and after practice an anonymous questionnaire was administered to understand the feelings and emotions. They have 47 students (97.9%) participated from 48 students, with a mean age is 20 ± 2.22 years. A 76.6% say they feel at the practice "Curiosity". Students have the highest percentage of unpleasant feeling "Odor" room (46.8%). Overall, students feel before starting "Quiet" and "Insurance" in 74.5% and 70.2%. There are 26 students (63.4%) who have expressed have had thoughts about life and death. 100% of students is recommended practice for upcoming courses with an average score of 9.1 points. The anatomy is usually an attractive subject for students and practices in the dissecting room generally involve a series of uncomfortable and stressful experiences. They have obtained similar to published results by others authors national and international. Passing a dissecting room can challenge the emotional balance of some students. Students consider this practice very useful.